THE INFLUENCE OF PROMOTIONS, PRICES AND BRAND AWARENESS ON ONLINE PURCHASING DECISIONS - Afi Lintang Cahyarani; Dadang Krisdianto; Daris Zunaida (Universitas Islam Malang, 2023)
The aim of the research was to determine the influence variables of promotion, price and brand awareness on Kaf's Dorayaki online purchasing decisions , both partially and simultaneously. The type of research used is quantitative. The population in this research is consumers who have made online purchases at Kaf's Dorayaki. This research provides results that promotion (X1) has a positive and significant effect on online purchasing decisions (Y) partially, namely t count > t table (3.625 > 2.018) and the significance value is 0.001 < 0.05. The price variable (X2) has a positive and significant effect on online purchasing decisions (Y) partially, namely t count > t table (2.780 > 2.018) and the significance value is 0.008 < 0.05. Brand awareness (X3) has a positive and significant effect on online purchasing decisions (Y) partially, namely t count > t table (3.135 > 2.018) and the significance value is 0.003 < 0.05. The F test showed that the three independent variables in this study simultaneously had a positive and significant effect on online purchasing decisions . Based on the R square test, it was found that online purchasing decisions (Y) were influenced 79.7% by the three independent variables and another 20.3% is influenced by other variables